Evaluation of TNF-alpha and IL-1 blockade in collagen-induced arthritis and comparison with combined anti-TNF-alpha/anti-CD4 therapy. - Williams, R; Marinova-Mutafchieva, L; Feldmann, M; Maini, R (2000)
We have evaluated the effects of anti-TNF-alpha, anti-IL-1, and combined anti-TNF-alpha/anti-CD4 therapy in collagen-induced arthritis. Blockade of TNF-alpha or IL-1 before disease onset delayed, but did not prevent, the induction of arthritis. When treatment was initiated after onset of arthritis, anti-TNF-alpha, anti-IL-1beta, and anti-IL-1R (which blocks IL-1alpha and IL-1beta) were all found to be effective in reducing the severity of arthritis, with anti-IL-1R and anti-IL-1beta showing greater efficacy than anti-TNF-alpha. Anti-IL-1beta was equally as effective as anti-IL-1R, indicating that IL-1beta plays a more prominent role than IL-1alpha in collagen-induced arthritis. An additive effect was observed between anti-TNF-alpha and anti-IL-1R in the prevention of joint erosion and in normalization of the levels of serum amyloid P. Combined anti-TNF-alpha/anti-CD4 therapy also caused normalization of serum amyloid P levels. The therapeutic effect of anti-TNF-alpha plus anti-CD4 was comparable to that of anti-TNF-alpha plus anti-IL-1R, suggesting that combined anti-TNF-alpha/anti-CD4 therapy prevents both TNF-alpha- and IL-1-mediated pathology. Anti-TNF-alpha treatment reduced IL-1beta expression in the joint and, conversely, anti-IL-1beta treatment reduced TNF-alpha expression. Combined anti-TNF-alpha/anti-CD4 treatment almost completely blocked the expression of IL-1beta, thereby confirming the ability of this form of combination therapy to prevent IL-1ss-mediated pathology.